Crustal structure of the Central Precordillera of San Juan, Argentina (31°S) using teleseismic receiver functions - Ammirati, Jean Baptiste (2013)
The subduction of the Nazca plate under the South American plate around 31°S is characterized by flat slab geometry. The (Chilean) Pampean flat slab of Argentina associated with the subduction of the Juan Fernandez ridge lies in a region of a series of foreland uplifts corresponding to the thin-skinned Precordillera and basement cored Sierras Pampeanas ranges. The SIEMBRA project deployed 40 broadband stations in 2008?2009 in both the Precordillera and the Sierras Pampeanas with the aim to foster the understanding of the entire central Andean flat slab region. One of the SIEMBRA station (DOCA) located on the western flank of Sierra de la Invernada in the Central Precordillera appears particularly appropriate to study the crustal structure and eventually detect discontinuities related to terranes establishment. We thus performed a receiver function analysis using teleseismic data recorded at the DOCA station during the SIEMBRA project and from October 2011 to June 2012 using a broadband UNSJ (National University of San Juan) seismic station with the purpose to obtain crustal images with details of the intracrustal structure consistent with a mechanism that could explains both the observed earthquake depths and the uplift pattern in the Central Precordillera. Our results show that the Moho beneath the Precordillera lies at a depth of about 66 km. The Moho signal appears diminished and behaves irregularly as a function of azimuthal orientations. Although this observation could be the result of an irregular geometry it also correlates with the hypothesis of partial eclogitisation in the lower crust. Two mid-crustal discontinuities have also been revealed. The shallower one could correspond to a décollement level between the Precordilleran strata and the Cuyania basement at 21 km depth. The deeper one which the presence has been matched with a sharp decrease of the crustal seismic activity drove us to the hypothesis of a major change in crustal composition at 36 km. Finally the flat portion of the subducted slab has been imaged lying at about 100 km depth.